DESKRIPSI KEMAMPUAN MATEMATIKA SISWA SMP DALAM MENYELESAIKAN SOAL MATEMATIKA TIPE PROGRAMME FOR INTERNATIONAL STUDENT ASSESSMENT (PISA) - Indrie Noor Aini; Ramlah Ramlah; Aan Subhan Pamungkas (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2021)
This research is motivated by the importance of mathematical literacy skills of junior high school students in solving PISA model questions. This study aims to describe the percentage at low, medium and high levels of students' ability in solving PISA questions. The type of research used is descriptive qualitative with the research subjects are 15 year old junior high school students. The data collection technique used is the method of observation, tests, interviews and documentation. The validity of the data in this study used a triangulation technique by comparing the data from tests, interviews and documentation to obtain the same data. The data analysis technique was carried out with data reduction steps, data presentation, verification and drawing conclusions. The result of knowledge is that students' ability to solve PISA type math problems with space and shape content is different. Most students are able to solve level 3 and 4 questions, while only a few students can solve level 5 questions. After the interview process, students did not understand what the question meant, students did not understand what was being asked.  Keywords:  student ability, PISA type math problems, PISA